Parenting Styles and Peer Influence as Correlates of Expressive Language Skills among Children with Autism Spectrum Disorder - Jacob, Udeme Samuel; Olorunniyi, Opeyemi Toluwani; Osisanya, Ayo; Pillay, Jace (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Introduction: It is more difficult for children with limited communication to understand the intentions of others and to communicate their own needs, feelings, and ideas because of their impaired expressive language skills. Objectives: This study investigated parenting styles and the peer-influence as correlates of expressive language skills in children with autism spectrum disorders. Methods: Convenient sampling was used to select 30 (male = 22; female = 8; age range 6 – 14 years old) children with an autism spectrum disorder. The instruments used for data collection were tagged Parenting Style Questionnaire, Peer Influence Questionnaire, and Expressive Language Skills Scale. The internal consistency of the Parenting Style Questionnaire, Peer Influence Questionnaire, and Expressive Language Skills Scale were Cronbach's > 0.70, 0.64, and 0.63, respectively. The scale suitability for participants was determined, and it yielded a Cronbach's α of 0.79. Results: The findings revealed that the different parenting styles, such as authoritative, authoritarian, permissive, and neglectful, had a positive relationship with expressive language skills of children with autism spectrum disorder, but the relation was not significant. Moreover, peer influence positively correlated with respondents’ language skills, but it was not significant. Conclusions: Based on the findings, it can be conclusively stated that regardless of parenting styles used, there was a positive relationship between respondents’ language skills, but the relationship was not significant. Therefore, further studies must be conducted to determine factors that are likely to contribute significantly to the language skills of children with an autism spectrum disorder.